A Window, Mirror, and Wall: How Educators Use Twitter for Professional Learning - Elizabeth Sturm; Laura Quaynor (Research in Social Sciences and Technology, 2020)
Teachers and other professionals increasingly utilize Twitter as a medium for professional expression and professional learning. These types of Twitter exchanges often take place in formal chats which are moderated by professional organizations or other knowledge brokers in the field. As moderated public online forums become more common, educators may wish to understand the benefits and limitations of this type of professional learning. This paper reports on a study of educators’ discourse in two hosted Twitter chats focused on global education and analyzes the ways in which these types of chats align with research on high-quality professional learning. Results indicate that Twitter chats provide multiple components of high-quality professional learning, namely a focus on content, collaboration, and teacher agency; to a lesser extent, they may provide peer coaching and allow for conversations across a sustained duration. However, other components of meaningful professional learning are not possible in this context, as it is not job-embedded and does not provide active learning or supported opportunities to practice.